The Construction of the Image of Contemporary China in the Translated Texts of News from the Perspective of Critical Discourse Analysis - Wang, Xinyu; Jia, Yan (International Journal of Social Sciences and Public Administration, 2025)
In the context of globalization, the construction and dissemination of national image has become an important part of international exchanges. As an important channel of cross-cultural communication, the translation of news has a crucial impact on shaping and disseminating the national image. Based on the theoretical framework of Fairclough’s three-dimensional model of critical discourse analysis and Halliday’s systemic-functional grammar, this paper makes an in-depth analysis of the translation of news documents in the bilingual section of China Daily’s official website, in order to explore whether China Daily embodies the application of transitivity system in the translation process, and how to convey China’s position and achievements through transitivity system, aiming to reveal the construction mode and effect of contemporary China’s image in foreign communication. This paper reveals the important role of news translation in shaping and spreading the image of contemporary China, and provides new ideas for foreign news translation.